1982
DOI: 10.1007/bf03189631
|View full text |Cite
|
Sign up to set email alerts
|

Fate and disposition of bromocriptine in animals and man. I: Structure elucidation of the metabolites

Abstract: A total of 16 metabolites of bromocriptine could be isolated from rat bile and incubates of rat liver cell preparations using [6-methyl-14C]bromocriptine as substrate. Separation and purification was achieved by reversed-phase liquid chromatography and preparative thin-layer chromatography in conjunction with radioactivity monitoring. Structure elucidation was based on spectroscopic data (UV, IR, NMR, EI- and FD-MS) and the results of amino acid analysis after acid hydrolysis. Based on the identified metabolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 4 publications
(5 reference statements)
2
53
0
Order By: Relevance
“…Before commencing any data analysis, the identity of one metabolite must be questioned, (Maurer et al, 1984). This metabolite is designated hereafter as metabolite X, although the identity of the metabolite is not crucial to the interpretation of the data.…”
Section: Discussionmentioning
confidence: 99%
“…Before commencing any data analysis, the identity of one metabolite must be questioned, (Maurer et al, 1984). This metabolite is designated hereafter as metabolite X, although the identity of the metabolite is not crucial to the interpretation of the data.…”
Section: Discussionmentioning
confidence: 99%
“…In some incubations, the formation of isobromocriptine and its hydroxylated metabolites was detected. These compounds derived from an epimerization at position 8 of the corresponding bromocriptine derivatives; they have been observed in the in vivo metabolism of bromocriptine (Maurer et al, 1982(Maurer et al, , 1983. The relative amounts of these isobromocriptine derivatives greatly depended on the time spent between the incubation and HPLC analysis.…”
Section: Rat and Human Microsome Incubationsmentioning
confidence: 99%
“…As metabolism of bromocriptine in vivo in rats and humans, and in rat hepatocytes, has been found to lead to stereoisomers of 8'-hydroxybromocriptine and 8',9'-dihydroxybromocriptine (Maurer et al, 1982(Maurer et al, , 1983 as main oxidation metabolites, it is very likely that metabolites MI and M, are the stereoisomers of 8'-hydroxybromocriptine while M, and M, are stereoisomers of 8',9'-dihydroxybromocriptine. Fig.…”
Section: Oxidation Of Bromocriptine By Rat and Human Liver Microsomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it has been demonstrated that Br is extensively metabolized in the liver of both animals and man and that hydrolysis, isomer ism and oxidation accounted for most of its metabolism (2 were determined by the method of Lowry et al (5), using bovine serum albumin as the standard. Cytochrome P-450 levels in micro somes were determined by the method of Omura and Sato (6).…”
Section: Brmentioning
confidence: 99%